Potential Works in BMR Transit-Oriented Development: Lesson Learned from The Past - Prasertsubpakij Garshasbi, Duangporn (Journal of Architectural/Planning Research and Studies (JARS), 2014)
This article aims to provide insightful discussions on how to make TOD works in Bangkok Metropolitan Region (BMR) according to the lesson learned from the past through a systematic review and discourse analysis. The findings indicated various hindrances to accomplish ‘the Avoid-Shift-Improve approach’ in BMR brought by dilemmas on metro unreachability, unplanned-structure of bus rapid transit, unpopularity of Suvar-nabhumi Airport Rail Link, non-integration of transportation and land use planning and silo practices. The study discoursed that unlike the foreign examples of TOD planning, mass rapid transits in BMR were initially built without any initiatives of TOD. The versions of TOD guidelines from other cities may not fit to the city; hence the study on multidimensional TOD practices must be performed to make TOD happen in BMR. Additionally, the potential works on creating TOD in the station areas involve collaboration among multiple stakeholders and land redevelopment associated with urban economics.